Jewish belief and practice in nineteenth century America : seminal essays by outstanding pulpit rabbis of the era - Gertel, Elliot (McFarland & Company, 2006)
"This anthology contains 18 essays written by 11 Jewish rabbis from 1856 to 1900. These thinkers dealt with issues such as providence, revelation, halakhah, evolution, biblical criticism, and science. The rabbis were popularizers, reformers, and traditionalists, and this collection bears those varied perspectives. The essays are presented in their original forms, but with footnotes added by the editor"--Provided by publisher.